Effect of the Educational Program about Puerperal Sepsis Prevention on knowledge and Practices of Pregnant Women - Abd-Elnaby Gad, Neveen Mohammed; Gad, Amany Hamed; Emarah, Hanan Abd-Elmohdy; Abdelmonem, Mervat Mostafa (Journal of Neonatal Surgery, 2024)
Background: One of the main causes of maternal death and a significant public health issue is puerperal sepsis. Aim of the study: To evaluate the effect of the educational program about puerperal sepsis prevention on knowledge and practices of pregnant women. Study design: A quasi experimental design was used. Setting: The study was conducted in in the outpatient antenatal clinic at Zagazig University Hospital. Study subjects: A purposive sample of 150 pregnant women. Tools of data collection: Three tools were used; tool I. A structured interview questionnaire, tool II. Pregnant women's knowledge assessment questionnaire, and tool III. Pregnant women's practices assessment questionnaire. Results: There was marked improvement in total women's knowledge and practices regarding puerperal sepsis prevention post intervention and two weeks after delivery compared to pre intervention with highly statistically significant difference, (P< 0.001). Conclusion: Applying the educational program significantly increased women knowledge and practices regarding prevention of puerperal sepsis. Also, there was significant relation between socio demographic variables and women knowledge and practice. Moreover, positive significant correlation between women knowledge and women practices. Recommendations: The antenatal clinics should be equipped with designed instructions booklet covering all knowledge and practices related to improving of pregnant women regarding puerperal sepsis prevention introduced to the women in the third trimester of pregnancy.